Optimal Operation Strategies Of Transformers For Third Rail System To Improve Energy Efficiency - Tan, Zhi Hao (2021)
The energy efficiency of railway systems is essentially important in lowering down the operational costs as well as reducing the carbon emission towards sustainable development. A typical third rail DC railway system is supplied from bulk supply substations (BSS) that are connected to the main grid. Thus, to maintain the reliability of the railway traction power systems, the BSSs are usually designed with additional power transformers in main-tie-main configuration. There are three operational modes for these transformers, namely non-parallel mode, parallel mode, and single transformer mode. Due to the fact that the traction loads are inherently dynamic, the optimal operation mode for the transformers requires a thorough simulation by including the train dynamics and train schedules. In this study, a comprehensive electrical model that includes the low voltage traction network and high voltage supply network of the Mass Rapid Transit 2 (MRT2) in Malaysia is developed. The model is developed using ETAP-Etrax software for dynamic load flow simulations to achieve an accurate estimation of transformer losses under the three transformer operation modes. The effects of train schedules to operating efficiency of transformer modes are investigated by including train headway interval variations. The results showed that the parallel mode has lower transformer losses than that of non-parallel mode for all the headway intervals, with a maximum loss reduction of up to 6.52%. It is also found that the single transformer mode has the lo west transformer losses for headway intervals of 5 minutes 48 seconds and above. Although the percentage of transformer loss reduction and the headway interval margin for optimal operation of single transformer mode may differ, this approach can also be ap plied to other DC railway systems.